Targeted Therapy for Chronic Spontaneous Urticaria: Rationale and Recent Progress - SALMAN, ANDAÇ (ADIS INT LTD, 2020)
Chronic spontaneous urticaria (CSU) is characterized by the presence of wheals, angioedema, or both for at least 6 weeks. It may persist for a long time-up to 50% of the patients have been reported to be symptomatic 5 years after the onset. Some patients can suffer more than one episode of CSU during their lifetime. Considering the recurrences, disabling symptoms, and significant impact on quality of life, proper and effective treatment of CSU is critical. The use of antihistamines (AHs) is still the mainstay of treatment. However, given the low rates of response to AHs (38.6% and 63.2% to standard doses and higher doses, respectively), the complete control of symptoms seems difficult to attain. The use of omalizumab for CSU has been a major breakthrough in the care of patients with CSU. However, the partial response and lack of response to omalizumab in a subgroup of patients, as high as 70% in some studies, make the development of alternative treatments desirable. Ever-increasing knowledge on the pathogenesis is making new target molecules available and enabling drug development for CSU. In addition to drug repurposing as in anti-IL-4/13, IL-5, and IL-17 antibodies, novel targeted therapy options such as ligelizumab and Bruton's tyrosine kinase inhibitors are currently undergoing clinical trials and will be available in the near future. This article reviews the current challenges in the treatment of CSU, the pathogenesis and potential target molecules, and the rationale for novel treatments and their rapidly developing status.
Keywords: CHRONIC IDIOPATHIC URTICARIA; CHRONIC AUTOIMMUNE URTICARIA; QUALITY-OF-LIFE; MAST-CELL; HISTAMINE-RELEASE; ANTI-SIGLEC-8 ANTIBODY; BASOPHIL ACTIVATION; GENE POLYMORPHISMS; COMPLETE REMISSION; CLINICAL ACTIVITY